Characterization of viral infections in children with influenza-like-illness during December 2018–January 2019 - Chao, Shuang; Wang, Yuejiao; Wu, Baolei; Li, Runqing; Dong, Jingxiao; Ji, Lina; Li, Xuejun; Li, Ran; Yin, Xiaomei; Zhao, Xiuying; Liang, Wannian (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction: Respiratory viral infection (RVI) is of very concern after the outbreak of COVID-19, especially in pediatric departments. Learning pathogen spectrum of RVI in children previous the epidemic of COVID-19 could provide another perspective for understanding RVI under current situation and help to prepare for the post COVID-19 infection control.old individuals respectively (P<0.05). In Summary, influenza viruses were the major pathogens in children with ILI during the 2018-2019 influenza epidemic, while hMPV and RSV were non-negligible. The coexistence of multiple pathogens leading to respiratory infections is the normalcy in winter ILI cases.